Law Enforcement of the Destruction of the Tanjung Panjang Nature Reserve Area in Randangan District - Ridwan Harun (Estudiante Law Journal, 2026)
This research aims to find outhow to enforce the law against the criminal act of destroying the Tanjung Panjang nature reserve area in Randangan District, and identify what factors hinder law enforcement. This research uses the type of empirical legal research, namely the type of research that wants to see how the application of law in society through the polarization of attitudes and actions. The data sources used are primary data sources consisting of observations and interviews as well as documentation, and secondary data which are supporting data in this study. The results of the study show that law enforcement is pursued through preventive measures in the form of outreach and education to the community around the area.Then there are also repressive efforts by taking legal channels.Obstacle factorThe problems faced by the Pohuwato Police are the process of proving or completing documents, difficulties in presenting or providing expert testimony, the alleged perpetrators are no longer in the location, and weak coordination between law enforcement officials and related institutions.